Fire Behavior, Weather, and Burn Severity of the 2007 Anaktuvuk River Tundra Fire, North Slope, Alaska - Jones, Benjamin M.; Kolden, Crystal A.; Jandt, Randi; Abatzoglou, John T.; Urban, Frank; Arp, Christopher D. (Arctic, antarctic, and alpine research, 2009)
In 2007, the Anaktuvuk River Fire (ARF) became the largest recorded tundra fire on the North Slope of Alaska. The ARF burned for nearly three months, consuming more than 100,000 ha. At its peak in early September, the ARF burned at a rate of 7000 ha d−1. The conditions potentially responsible for this large tundra fire include modeled record high summer temperature and record low summer precipitation, a late-season high-pressure system located over the Beaufort Sea, extremely dry soil conditions throughout the summer, and sustained southerly winds during the period of vegetation senescence. Burn severity mapping revealed that more than 80% of the ARF burned at moderate to extreme severity, while the nearby Kuparuk River Fire remained small and burned at predominantly (80%) low severity. While this study provides information that may aid in the prediction of future large tundra fires in northern Alaska, the fact that three other tundra fires that occurred in 2007 combined to burn less than 1000 ha suggests site specific complexities associated with tundra fires on the North Slope, which may hamper the development of tundra fire forecasting models.